STRATEGI GURU DALAM MENGEMBANGKAN KETERAMPILAN BERBICARA ANAK DENGAN MENGGUNAKAN METODE BERMAIN PERAN - Yusniar Yusniar; Widya Masitah (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
This study aims to find out how the teacher's strategy is in developing speaking skills in children aged 5-6 years using the role playing method at RA Al-Musthafawiyah, Medan Tembung District. The method used in this study uses qualitative research methods. Data collection techniques used in this study include interviews, observation and documentation as well as data analysis techniques using the Miles and Huberman Interactive data analysis model. The data validation technique uses the triangulation method. Based on the results of the research and data analysis, it can be concluded that the teacher's strategy in developing children's skills using the role playing method works well, it's just that there are obstacles in some children who are not proficient in developing their speaking skills. The strategy carried out by the teacher is to first prepare learning plans such as preparing Semester Programs (Prosem), Learning Implementation Plans (RPP), Weekly Learning Implementation Plans (RPPM), and Daily Learning Implementation Plans (RPPH). This is done in order to achieve a certain goal that is done as well as possible and as much as possible in accordance with the goals achieved. In addition, teachers also use supporting strategies. In addition, teachers also use other supporting strategies, namely carrying out habituation activities that are carried out every day. The causes that make children's speaking skills not develop optimally are the lack of communication between children and parents, children feel insecure when talking to other people, environmental factors that become obstacles to children's speech, lack of stimulation in children, children prefer to be alone, children are afraid in mentioning new vocabulary.